Enhancing Accountability and Governance in Local Communities through ISAK 335 Financial Systems - Yuhertiana, Indrawati; Indah kirana, Nanda wahyu; Hardjatie, Susi; Tannar, Oriza; Wati, Seftin Fitri Ana; Edo, Kalvin; Suryaningrum, Diah Hari (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study explores the application of digital financial systems grounded in ISAK 35 to enhance accountability and governance within the RW 02 community in Kelurahan Kalisari, Surabaya. The program employed a Community-Based Research (CBR) methodology to rectify inefficiencies in manual financial reporting by implementing a digitalized system, concurrently including stakeholders in a participatory framework. The project produced substantial results, such as heightened community trust, improved decision-making via precise financial reporting, and augmented donor confidence in fund management. Nonetheless, obstacles such as disparate digital literacy levels and the maintenance of prolonged involvement surfaced, underscoring the necessity for intuitive solutions and specialized capacity-building initiatives. By incorporating lessons learned into academic curricula and utilizing participatory monitoring and evaluation, the initiative connected theory with practice. This effort provides critical insights for policymakers and practitioners, highlighting the significance of transparency, community empowerment, and scalable solutions in financial governance. Subsequent study must concentrate on guaranteeing sustainability and investigating the applicability of analogous systems in various circumstances. The project produced substantial results, such as heightened community trust, refined decision-making via precise financial reporting, and augmented donor confidence in fund administration.